2018
DOI: 10.3390/w10030323
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Monitoring of Suspended Sediment Variations for Water Quality Evaluation at Deep Bay, Pearl River Estuary, China: Influence Factors and Implications for Sampling Strategy

Abstract: Suspended sediment (SS) is an important water quality indicator of coastal and estuarine ecosystems. Field measurement and satellite remote sensing are the most common approaches for water quality monitoring. However, the efficiency and precision of both methods are typically affected by their sampling strategy (time and interval), especially in highly dynamic coastal and estuarine waters, because only limited measurements are available to analyze the short-term variations or the long-term trends of SS. Dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…So it can be concluded that the tide is the dominant factor influencing the variation of suspended sediment concentration. Similar results were found in Deep Bay, Pearl River Estuary, China [30]. Besides, the diffusion phenomenon of suspended load is well reproduced in Figure 9.…”
Section: Boundary Conditionssupporting
confidence: 84%
“…So it can be concluded that the tide is the dominant factor influencing the variation of suspended sediment concentration. Similar results were found in Deep Bay, Pearl River Estuary, China [30]. Besides, the diffusion phenomenon of suspended load is well reproduced in Figure 9.…”
Section: Boundary Conditionssupporting
confidence: 84%
“…This study examines the potential of the AHI sensor for monitoring the coastal surface TSS, as the AHI sensor is deployed with suitable wavebands of visible, Near Infrared (NIR) and Shortwave Infrared (SWIR), and high temporal resolution (every 10 min). The Pearl River Estuary (PRE) and neighboring coastal waters were selected, showing relatively strong daily sedimentary and runoff variations [33]. Additionally, the marine ecosystem adjacent to the PRE is disturbed by the problem of sediment and effluent runoff from rapid industrial and urban development [34]; high-frequency mapping of TSS is, thus, critical for monitoring the coastal ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…In estuaries, flood and ebb tides normally lead to the mixing of inland riverine water with seawater from the surrounding bay as well as the surface and bottom water [31,32]. In our study, the concentrations of F. Coli and physiochemical parameters in the surface and bottom water were generally consistent during flood and ebb tides ( Figure 2), suggesting that the effect of tides on hydrological exchange in the sampling sites was very weak.…”
Section: Microbiological and Physiochemical Parametersmentioning
confidence: 51%